Östliches Rifgebirge, Marokko - Eiwanger, Josef (e-Forschungsberichte des DAI, 2023)
During 2012 and 2013 the DAI/KAAK-project “Prehistory and Protohistory of the Eastern Rif Mountains in Morocco” in cooperation with the National Institute of Archaeology and Patrimony (Rabat, Morocco) has been continued. The research focussed on the rockshelter of Ifri n’Ammar in the eastern outskirts of the Rif. Beside the former excavations which furnished a stratigraphy dating between 180 000 and 10 000 years a new surface in the center of the site has been opened. The main reason was to receive more information about the spatial archaeology of this important site. In 2012–2013 the layers of the upper Atérien technocomplex have been excavated. Beside this, a comprehensive study on the traseology of Atérien silex tools has been started.